Adaptive evolution of the osmoregulation-related genes in cetaceans during secondary aquatic adaptation - Xu, Shixia (BioMed Central, 2013)
BACKGROUND: Osmoregulation was a primary challenge for cetaceans during the evolutionary transition from a terrestrial to a mainly hyperosmotic environment. Several physiological mechanisms have been suggested to maintain the water and salt balance in cetaceans, but their genetic and evolutionary bases remain poorly explored. The current study investigated the genes involved in osmoregulation in cetaceans and compared them with their counterparts in terrestrial mammals to test whether adaptive evolution occurred during secondary aquatic adaptation. RESULTS: The present study analyzed the molecular evolution of 11 osmoregulation-related genes in 11 cetacean species, which represented all of the major cetacean clades. The results demonstrated positive selection acting on angiotensin converting enzyme (ACE), angiotensinogen (AGT), SLC14A2, and aquaporin 2 (AQP2). This evidence for the positive selection of AQP2 and SLC14A2 suggests that the adaptive evolution of these genes has helped to enhance the capacity for water and urea transport, thereby leading to the concentration of urine, which is an efficient mechanism for maintaining the water balance. By contrast, a series of positively selected amino acid residues identified in the ACE and AGT (two key members of the renin-angiotensin-aldosterone system, RAAS) proteins of cetaceans suggests that RAAS might have been adapted to maintain the water and salt balance in response to a hyperosmotic environment. Radical amino acid changes in positively selected sites were distributed among most internal and terminal branches of the cetacean phylogeny, which suggests the pervasively adaptive evolution of osmoregulation since the origin of cetaceans and their subsequent diversification. CONCLUSIONS: This is the first comprehensive analysis of the molecular evolution of osmoregulation-related genes in cetaceans in response to selection pressure from a generally hyperosmotic environment. Four genes, i.e., AQP2, SLC14A2, ACE, and AGT were subject to positive selection in cetaceans, which suggests that cetaceans may have adapted to maintain their water and salt balance. This also suggests that cetaceans may have evolved an effective and complex mechanism for osmoregulation.